LARIK TRADITION AS AN ETHNOSPORT: MOVEMENT ANALYSIS AND IMPLICATIONS FOR PHYSICAL EDUCATION BASED ON LOCAL WISDOM - Robertus Lili Bile (Universitas Labuhanbatu, 2026)
Purpose – This study aims to reveal the unique features of the traditional Larik dance of the Riung Barat ethnic community in Ngada Regency and to analyze how its movement elements and cultural values provide practical implications for developing a physical education curriculum grounded in local wisdom.Methodology – The study used an interpretive-phenomenological qualitative approach, involving 14 key informants (9 active fighters, 3 traditional referees, 2 traditional leaders) from Maronggela, where the larik tradition is practiced. Data were collected through participant observation during 5 Larik sessions, semi-structured in-depth interviews, focus group discussions, document studies, and functional movement analysis of 120 purposively selected video segments.Findings – Larik is a turn-based whip duel using buffalo leather whips and curved bamboo shields, as well as round buffalo leather shields, with strict rules regarding only the upper body. Functional movement analysis shows six dominant categories: ready position/low stance (36.7%), whip attacks (31.7%), active defense with shields (13.3%), dodging/twisting (10.0%), footwork (5.0%), and recovery/transition rituals (4.3%). The three main cultural values embedded in this activity are gratitude to God and ancestors, predictions of the harvest, and solidarity between tribes.Contribution – This study provides a theoretical contribution in the form of the first scientific documentation of the characteristics of Larik as an ethnosport, as well as a practical contribution in the form of recommendations for integrating Larik into the physical education curriculum to develop balance, agility, hand-eye coordination, explosive power, sportsmanship, courage, and a sense of brotherhood among students.